Organizing Knowledge for Environmentally and Socially Sustainable Development - Serageldin, Ismail; Unesco; World Bank. (Washington, DC: World Bank, 1998)
For development to be done differently, those being educated must be empowered tp perceive and connect their disciplines differently, and to develop knowledge that will be useful for decision-makers outside the academic and research worlds. Thus, this publication explores the critical tasks confronting educators and development practitioners, and the need for a new discourse between them.
Proceedings of a concurrent meeting of the fifth annual World Bank Conference on Environmentally and Socially Sustainable Development, partnerships for global ecosystem management, science, economics and law : cosponsored by UNESCO and the World Bank and held at the World Bank, Washington, D.C., October 9-10, 1997.
Includes bibliographical references.
ne 15/05/2018
Ref
Keywords: Sustainable development